The Development of the Method for the Calculation of the Shaping Force in the Production of Vehicle Wheel Rims - Puzyr, Ruslan; Kukhar, Volodymyr; Maslov, Alexander; Shchipkovsky, Yevhenii (International Journal of Engineering and Technology, 2018)
The objective of the paper is the development of the method for the calculation of the required force of shaping of a horizontal shape-forming machine used in the preproduction workflow. The design of a machine for horizontal shape-forming of wheel steel rims enables quick readjusting and transfer to another rim shape, which is significant under the conditions of frequent alteration of the product nomenclature. We developed the calculation method based on the assumptions of the deformations continuity, the constancy of the volume at plastic deformation and axisymmetric stressed state as well as the local application of the load. The research resulted in obtaining the analytical dependences for the calculation of the force of shaping of a wheel rim, taking into account the degree of deformation, the mechanical characteristics of the metal, hardening as well as the design and technological factors of the process. The topicality of the development consists in the necessity for the high-quality and the least expensive choice of the equipment of the required rated power when designing a new workflow. The experimental data, carried out both under the production and laboratory conditions, confirmed the adequacy of the theoretical formulas. It is determined by the assumptions and solutions obtained based on the mathematical apparatus of the technical theory of the shells of revolution. The clearness of the method will make it possible to algorithmize the calculation process quite easily and to use it as a subprogram in an applied complex of technical preproduction. It will also allow determining the shaping process most significant factors influencing the value of the force without the direct use of the calculation. We recommend to use it at enterprises producing vehicle steel wheels by the method of radial-rotation shaping.Â Â
Keywords: closed shell; deformation hardening; force of shaping; plastic deformation; wheel rim.